The terror: a novel - Simmons, Dan (London Transworld Publishers, 2008)
Cut from the Cleveland Browns after the worst performance in the history of the NFL, Rick Dockery, desperate to play football, is hired by the Panthers of Parma, Italy, and finds himself confronted by the confusing diversity of Italian culture, language,and romance.
Keywords: Americans -- Italy; Football stories; Sports stories; Italy